The shadow thieves - Ursu, Anne. (New York : Aladdin Paperbacks, 2007)
After her cousin Zee arrives from England, thirteen-year- old Charlotte and he must set out to save humankind from denizens of the underworld, Nightmares, Death, Pain, and a really nasty guy named Phil.
850
Accelerated Reader AR
Keywords: Animals, Mythical -- Juvenile fiction; Cousins -- Juvenile fiction; Good and evil -- Juvenile fiction; Animals, Mythical -- Fiction; Cousins -- Fiction; Good and evil -- Fiction; Fantasy; Fantasy fiction